HYBRID CLOUD INFRASTRUCTURE VS. ON-PREMISES: SECURITY, PERFORMANCE, AND COST PERSPECTIVES (Modern education and development, 2025)
This article analyzes the differences and features of hybrid cloud infrastructure and on-premises deployment models in terms of security, performance, and cost. The advantages and disadvantages of both models are considered, and recommendations are made on which infrastructure model is more effective for organizations. The article highlights the main factors that are important in choosing a modern IT infrastructure.